PELATIHAN MISIOLOGI PRAKTIS UNTUK PENGUATAN KESAKSIAN GEREJA BAGI JEMAAT GEREJA PENTAKOSTA INDONESIA LIPPO CIKARANG - Siregar, Elia H; Marbun, Obtamar; Siregar, Parulian (PUAN INDONESIA, 2026)
This community service article examines a practical missiology training program aimed at strengthening church witness among members of the Gereja Pentakosta Indonesia, Lippo Cikarang. The church’s mission is often limited to internal religious activities, while its broader missional calling in daily social contexts remains underdeveloped. This condition is particularly evident in urban–industrial areas characterized by social diversity, high mobility, and economic pressure. The program was designed to equip church members with contextual and practical missiological understanding, emphasizing mission as a holistic expression of faith integrated into everyday life. The training employed a participatory–reflective approach through contextual analysis, group discussions, and practical reflections on family, workplace, and community settings. The results indicate increased awareness of mission as a shared responsibility of all believers, improved understanding of holistic mission, and a positive shift in attitudes toward everyday Christian witness. Participants demonstrated greater confidence in integrating faith values into social relationships and professional life. The findings suggest that practical missiology training effectively empowers congregations to become active agents of mission, enhancing the relevance and impact of church witness in contemporary society.